The Basic Categories and Assumptions for Contemporary Chinese Argumentation Studies (Sinología hispánica. China Studies Review, 2016)
A systemic study of argumentation indefinition, stages, types, techniques, andprinciples of argumentation has been reflected.Based on this reflection, the basic assumptionsof contemporary Chinese argumentation studieshave been drawn upon. Finally, the underlyingreasons for the present situation have beenanalyzed.